Oscillation Criteria Of Third Order Nonlinear Neutral Differential equations - Soliman, A.A.; Sallam, R.A.; Elbitar, A.; Hassan, A.M. (International Journal of Applied Mathematical Research, 2012)
In this paper we will study the criteria for oscillation of the equation[a(t)(z"(t))]' +_j=1^m fj(t; x(j(t))) = 0and establish new oscillation criteria some examples of the obtained results are given.Our technique is Riccati's method.Keywords: Oscillation, Third order, Nonlinear equation, Neutral type.